Presence of moulds and mycotoxins in spices - Karan Dragica D.; Vukojević Jelena B.; Milićević Dragan R.; Ljajević Milica-Grbić V.; Janković Vesna V. (Zbornik Matice Srpske za Prirodne Nauke, 2005)
In this paper there are presented the results of mycologic and mycotoxicologic analysis of seven spices which are being used for production of meat products. Using standard mycologic methods, in all the tested samples, we noticed a presence of moulds. By quality and quantity, most represented are genera: Aspergillus and Penicillium. With smaller occurrence there are presented genera: Rhizopus, Mucor, Paecylomyces and Absydia. Mycotoxins - ochratoxin, aflatoxins and zearalenon, are detected in samples of ground white pepper, ginger, cloves and ground caraway.